Snailfishes (Family Liparidae) of the Ross Sea, Antarctica, and Closely Adjacent Waters - Stein, David L. (Zootaxa, 2012)
Snailfishes (Family Liparidae) of the Ross Sea are reviewed, keys are provided to their identification, and the utility ofseveral taxonomic characters, including the pectoral fin and girdle and length and shape of the abdominal cavity, is dis-cussed. New and previously unstudied specimens show that there are more than 34 Ross Sea liparid species in three gen-era; 18 of them are new to science and are described below. Ross Sea snailfishes include at least six Careproctus, 27Paraliparis, and one Genioliparis species. The new species are Paraliparis alius from off Iselin Seamount at 1225–1332m, P. amerismos from off Hillary Canyon (near Pennell Bank) at 1149–1358 m, P. camilarus from the northwest edge ofMawson Bank at 1431–1658 m, P. ekaporus from off Mawson Bank at 1431–1658 m, P. epacrognathus from off MawsonBank at 1431–1658 m, P. haploporus from off Mawson Bank at 1954–1990 m, P. longicaecus from the NW edge of Maw-son Bank at 1431–1658 m, P. macropterus from off Iselin and Mawson Banks at 1133–1990 m, P. magnoculus from offIselin and Scott Canyon at 950–1368 m, P. mentikoilon from off Mawson Bank at 1954–1990 m, P. nigrolineatus from offMawson Bank at 1954–1990 m, P. nullansa from off Mawson Bank at 1954–1990 m , P. orbitalis from off Cape Adare at 1110–1210 m, P. parviradialis from off Mawson Bank at 1954–1990 m, P. plicatus from off Mawson Bank at 1431–1990m, P. posteroporus from off Mawson Bank at 1400–1600 m, P. tangaroa from Iselin Seamount at 966–1153 m, and P.voroninorum from off Mawson Bank at 1954–1990 m. In addition, one unknown Paraliparis is partially described but notnamed owing to its poor condition. Range extensions for P. neelovi and P. stehmanni are reported, and two more individ-uals of P. andriashevi, previously known from two specimens, were collected. Other species included are Careproctus am-pliceps, C. catherinae, C. inflexidens, C. polarsterni, C. pseudoprofundicola, C. vladibeckeri, Genioliparis kafanovi,Paraliparis antarcticus, P. devriesi, P. fuscolingua, P. macrocephalus, P. rossi, and P. terraenovae. History and character-istics of the Ross Sea that probably led to isolation and speciation are described and discussed. The new discoveries increase the number of known Southern Hemisphere snailfish species to about 200.